Diskursus Literasi Abad 21 di Indonesia - Dipa Nugraha; Dian Octavianah (Jurnal Pendidikan Edutama, 2020)
Abstract: This study is to describe discourse on literacy in Indonesia. This study used an extensive survey of related literature on literacy which was accessed on Google Cendekia in December 2019 using â€œliterasi abad 21â€ as its keyword. The analysis is descriptive qualitative. This study concludes that: First, discourse on literacy in Indonesia started with the governmentâ€™s National Literacy Movement in 2015. The discourse on literacy in Indonesia is based on New Vision for Education: Unlocking the Potential of Technology a framework for 21st century education from World Economic Forum and Boston Consulting Group, PISA 2015 Assessment and Analytical Framework from OECD, and 21st Century Skills Map from The Partnership for 21st Century Learning. Second, there are nineteen literacies discussed and developed within the discourse. However, environmental literacy and ecological literacy are absent, or at least lacking compared to the other nineteen literacies in the conversation. Considering environmental literacy and ecological literacy are both important for the future of Indonesia, it is suggested that Indonesian scholars in education should start talking more about these literacies in the conversation on literacy and their importance in Indonesian education.Â Keywords: literacy, 21st century literacy, Indonesian literacy.Â Abstrak: Penelitian ini mendeskripsikan diskursus mengenai literasi di Indonesia. Penelitian ini menggunakan survei daring dengan menggunakan Google Cendekia dengan kata kunci â€œliterasi abad 21â€ yang dilakukan di bulan Desember 2019. Analisis dilakukan dengan menggunakan metode deskriptif kualitatif. Hasil dari penelitian ini ada dua. Pertama, diskursus mengenai literasi di Indonesia dimulai dengan Gerakan Literasi Nasional di tahun 2015. Diskursus mengenai literasi di Indonesia didasarkan atas tiga rujukan kerangka kerja pendidikan yaitu New Vision for Education: Unlocking the Potential of Technology dari World Economic Forum and Boston Consulting Group, PISA 2015 Assessment and Analytical Framework dari OECD, dan 21st Century Skills Map dari The Partnership for 21st Century Learning. Kedua, terdapat sembilan belas literasi yang dibicarakan dan berkembang di dalam diskursus mengenai literasi di Indonesia. Meskipun demikian, literasi lingkungan dan ekologi tidak muncul atau kurang dibicarakan. Menimbang bahwa literasi lingkungan dan ekologi penting bagi masa depan Indonesia, penelitian ini memberikan saran perlunya pembelajaran literasi ini tidak hanya mulai kencang dibicarakan tetapi juga urgensi implementasinya di dunia pendidikan di Indonesia Â Kata kunci: literasi, literasi abad 21, literasi Indonesia Â